2021
DOI: 10.1111/gcb.15927
|View full text |Cite
|
Sign up to set email alerts
|

Warming increased bark beetle‐induced tree mortality by 30% during an extreme drought in California

Abstract: Quantifying the responses of forest disturbances to climate warming is critical to our understanding of carbon cycles and energy balances of the Earth system. The impact of warming on bark beetle outbreaks is complex as multiple drivers of these events may respond differently to warming. Using a novel model of bark beetle biology and host tree interactions, we assessed how contemporary warming affected western pine beetle (Dendroctonus brevicomis) populations and mortality of its host, ponderosa pine (Pinus po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
33
1
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 52 publications
(38 citation statements)
references
References 65 publications
(110 reference statements)
1
33
1
3
Order By: Relevance
“…We found that while most mortality prior to the drought was concentrated in smaller size classes of overstory trees, drought and beetle-related mortality shifted patterns of tree mortality to be more evenly distributed across size classes and concentrated in species of pine (Fig. 2); these findings align with several other studies reporting patterns of the recent California tree mortality event (Fettig et al 2019;Koontz et al 2021;Robbins et al 2022). We observed substantial changes to Quadratic mean diameter (cm) 2.7 ± 0.4 1.9 ± 0.3 surface fuel loading, stand density metrics, canopy fuel loads, and potential wildfire emissions over a sampling period of just four years beyond when most tree mortality occurred.…”
Section: Discussionsupporting
confidence: 90%
“…We found that while most mortality prior to the drought was concentrated in smaller size classes of overstory trees, drought and beetle-related mortality shifted patterns of tree mortality to be more evenly distributed across size classes and concentrated in species of pine (Fig. 2); these findings align with several other studies reporting patterns of the recent California tree mortality event (Fettig et al 2019;Koontz et al 2021;Robbins et al 2022). We observed substantial changes to Quadratic mean diameter (cm) 2.7 ± 0.4 1.9 ± 0.3 surface fuel loading, stand density metrics, canopy fuel loads, and potential wildfire emissions over a sampling period of just four years beyond when most tree mortality occurred.…”
Section: Discussionsupporting
confidence: 90%
“…Our analysis does not distinguish abiotic disturbances such as windthrow and frost damage that have no linkage to droughts; however, these types of disturbance are substantially less frequent compared to fire, insects and harvest and therefore the bias should be relatively small. The drought-associated carbon loss could be partially linked to potential weakening of tree defense against insects and diseases during drought (Anderegg et al, 2015;Huang et al, 2020;Robbins et al, 2022). To test this hypothesis, we conducted additional analyses to assess whether drought played a role in insect/disease-caused disturbances by comparing the mean ESI values of pixels affected by as insect/disease that were defined by the US IDS database to pixels within a region.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have documented adverse effects on vegetation communities as a result of the changing climate and changing wildfire regimes in California (Williams et al 2019, Huesca et al 2021. Nonetheless, most of the studies were confined to specific vegetation groups or few species, specific drought incidents, or analysis over a relatively short annual time period (Baguskas et al 2014, Taylor et al 2019, Baeza et al 2021, Wayman and Safford 2021, Robbins et al 2022; thus, limiting our understanding of the broadscale effects on tree cover as well as the spatiotemporal variability of effects among ecoregions across California. In this study, we used multiple annual land cover and land surface change products from the U.S. Geological Survey's (USGS) Land Change Monitoring, Assessment and Projection (LCMAP) product suite to assess patterns in tree cover loss in eight tree-dominated ecoregions in California from 1986 to 2019.…”
Section: Introductionmentioning
confidence: 99%